-8(4b+3)+(33b-7)=0

Simple and best practice solution for -8(4b+3)+(33b-7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(4b+3)+(33b-7)=0 equation:


Simplifying
-8(4b + 3) + (33b + -7) = 0

Reorder the terms:
-8(3 + 4b) + (33b + -7) = 0
(3 * -8 + 4b * -8) + (33b + -7) = 0
(-24 + -32b) + (33b + -7) = 0

Reorder the terms:
-24 + -32b + (-7 + 33b) = 0

Remove parenthesis around (-7 + 33b)
-24 + -32b + -7 + 33b = 0

Reorder the terms:
-24 + -7 + -32b + 33b = 0

Combine like terms: -24 + -7 = -31
-31 + -32b + 33b = 0

Combine like terms: -32b + 33b = 1b
-31 + 1b = 0

Solving
-31 + 1b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '31' to each side of the equation.
-31 + 31 + 1b = 0 + 31

Combine like terms: -31 + 31 = 0
0 + 1b = 0 + 31
1b = 0 + 31

Combine like terms: 0 + 31 = 31
1b = 31

Divide each side by '1'.
b = 31

Simplifying
b = 31

See similar equations:

| 7x-9=3(x+5) | | 1.3x-2.39=5.67x+4.74 | | b+5=-10 | | .75a-.666=.583 | | 3(4-5k)-5(7-2k)+6=3k+7 | | .3333333334z-4=-.3333333334z+18 | | z^2+9z-9=(2z+3)(z-3) | | 2v^3-3v^2-14v+21=0 | | 6(x-3)=2x+4-6 | | 4-49v^2=0 | | -3/4+(-3/4)=0 | | -6x+16=-2x | | .5d=2-.5d | | 2/5+1/5=0 | | 4.8q-5.9-5.7q=-1.9q-4.2 | | 1.3p+0.3p-2=1.2 | | 15a^2+a=2 | | 4(4x-5)= | | 9x^2+15x+52=352 | | 2x^2+3y^2-2xy=10 | | 7y^2+23y=20 | | 8(2+x)=3x-14 | | 108-2x=34x+20 | | 3(z-7)=18 | | 30v^3x^9+9v^2x^6y^4=0 | | 6-3(3x-2)=-6 | | 3(2-7)=18 | | 5x-(2x+12)=3(x-4) | | 6(.5b+3)+4(12-b)=0.83 | | x^2+30y^2=1 | | -2+3x=-(x-6) | | 6(.5b+3)+4(12-b)=5 |

Equations solver categories